2010
DOI: 10.1016/j.parkreldis.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The safety of transcranial magnetic stimulation with deep brain stimulation instruments

Abstract: Objectives: Transcranial magnetic stimulation (TMS) has been employed in patients with an implanted deep brain stimulation (DBS) device. We investigated the safety of TMS using simulation models with an implanted DBS device. Methods: The DBS lead was inserted into plastic phantoms filled with dilute gelatin showing impedance similar to that of human brain. TMS was performed with three different types of magnetic coil. During TMS (1) electrode movement, (2) temperature change around the lead, and (3) TMS-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
2
24
0
1
Order By: Relevance
“…Several ex vivo studies showed that TMS over DBS leads did not induce sufficient current to cause tissue damage or damage to the pulse generator (Kuhn and Huebl, 2011; Kumar et al, 1999), although stimulation over lead loops could potentially produce current large enough to be dangerous (Deng et al, 2010; Shimojima et al, 2010). At least 20 TMS studies in patients with DBS have been published since 2001 (Chen et al, 2001) and no AEs have been reported.…”
Section: The Application Of Low Intensity Tes In Human Studies: Aementioning
confidence: 99%
“…Several ex vivo studies showed that TMS over DBS leads did not induce sufficient current to cause tissue damage or damage to the pulse generator (Kuhn and Huebl, 2011; Kumar et al, 1999), although stimulation over lead loops could potentially produce current large enough to be dangerous (Deng et al, 2010; Shimojima et al, 2010). At least 20 TMS studies in patients with DBS have been published since 2001 (Chen et al, 2001) and no AEs have been reported.…”
Section: The Application Of Low Intensity Tes In Human Studies: Aementioning
confidence: 99%
“…For example, if TMS is applied to a subject simultaneously receiving some form of transcranial electric stimulation (e.g., tDCS), the TMS magnetic field could potentially induce unintended currents in the scalp electrodes and leads, thus confounding the experimental paradigm and potentially compromising safety. Studies on the interactions between TMS and transcranial electric stimulation devices are currently lacking, but caution is warranted as significant currents induced by TMS in the leads and electrodes of deep brain stimulation implants have been reported (98,99). …”
Section: Dose Definition and Dose Selectionmentioning
confidence: 99%
“…Intracranial EEG recordings in patients evaluated for pharmacoresistant epilepsy, for instance, would also extend the spatial capacity of this approach and allow studying of the deeper structures of the thalamocortical networks. Previous studies have demonstrated the safety of using TMS with implanted electrodes, although some recommendations have been released; such as avoiding stimulation near electrodes loops and avoiding repetitive TMS in a chronic setting due to lack of data on potential tissue damage [75].…”
Section: Future Perspectivesmentioning
confidence: 99%